Kearifan Lokal Makna Simbolik Perahu Batu Pada Tradisi Masyarakat Desa Sangliat Dol Kecamatan Wertambrian Kabupaten Kepuluan Tanimbar - Nifmaskossu, Regina; Kewilaa, Deby Marlina (Peneliti.net, 2022)
The stone boats in Sangliat Dol village are an invaluable inheritance from their anceestors, produced by the ancestors as a traditional legacy for their successors. The stone boat is also a characteristics portrait of the community itself which reflects the beauty , balance and simplicity of the stone boat itself. Therefore, if studied in depth, it will be known the noble values that live and develop in society itself. Stone boats have symbols that contain implied meaning, so it is very important to know. The meanings and symbols contained in the stone boat are 1)a carving on one of the steps, 2) four upright stones, 3) a stone altar, 4) a bird motif on the stone boat natar, 5) the stern of the boat , 6) a standing stone on the stern part. The aim of this research is to describe the local wisdom of the symbolic meaning of stone boats in the Sangliat dol village community. The method used is a qualitative method with a descriptive design, namely research that provides a careful description of certain individuals or groups regarding the conditions and symptoms that occur